URGENSI PELESTARIAN LINGKUNGAN DI ERA REVORMASI 4.0 - Hasan, Mohamad Ali; Ardiansyah, Mukhammad Fajar; Khovivah, Siti Nur (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
In the era of Industrial Revolution 4.0, environmental preservation has a very important urgency. The environmental paradigm in this era is the main concern in maintaining the sustainability and balance of the ecosystem. Environmental preservation is becoming increasingly important in this era. Industrial Revolution 4.0 brought major changes in various sectors, including industry, technology and transportation. However, these changes also have negative impacts on the environment, such as increased greenhouse gas emissions, air pollution and ecosystem damage. Environmental preservation in the era of Industrial Revolution 4.0 has high urgency. In facing the challenges of change brought by the Industrial Revolution 4.0, there needs to be awareness and collective action from all parties, both individuals and industry players, to preserve the environment. Therefore, researchers have taken this title with great hopes that it can become reference material for readers and increase our insight and knowledge so that the environment, especially around us, can be preserved.